Educação na Pandemia: Experiências com os anos iniciais do ensino fundamental em escolas da cidade de Sorocaba - Silveiras, Heloísa Coes (Universidade Federal de São Carlos, 2023)
The present work is the culmination of an academic path, outlining the memories of a student of the Pedagogy course at the Federal University of São Carlos - Campus Sorocaba, during the unfolding of the Covid-19 pandemic. The experiences took place in the early years of elementary school, in two different schools – one public and the other private – in the city of Sorocaba, located in the interior of the state of São Paulo. The focus of the research lies on analyzing the approaches adopted by each institution in the context of the pandemic, outlining the nuances of education during this challenging period. The purpose is to encourage reflection on the value of these experiences for the author's growth and development as a future educator. The methodology employed comprises a foray into memories, allowing the recovery of past experiences in addition to the careful analysis of the reports generated during the mandatory and non-mandatory internships, as well as the reports produced during the Pedagogical Residency Program, and how all of these contributed to the enrichment of the investigative approach.
Education in the Pandemic: Experiences with the initial years of elementary school in schools in the city of Sorocaba
Keywords: educação; pandemia; anos iniciais; education; pandemic; early years; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO